ANALISIS PENGARUH TEKANAN, PELUANG, RASIONALISASI, DAN KAPABILITAS TERHADAP KEMUNGKINAN KECURANGAN LAPORAN KEUANGAN: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Zahra Rohadotul Aisy Solikhin; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2023)
Fraudulent financial statement is a fraudulent scheme in the form of deliberate misstatements by eliminating material information in the organization's financial statements. Fraudulent financial statement occurs due to several factors, one of which is explained in the diamond fraud theory proposed by Wolfe and Hermanson (2004), namely pressure, opportunity, rationalization, and capability. This study aims to analyze the influence of elements of diamond fraud theory, represented into financial stability, external pressures, financial targets, industry nature, monitoring effectiveness, turnover of external auditors, and change of directors, on the possibility of fraudulent financial statement. The samples used in this study consisted of 465 samples from 93 manufacturing companies listed on the IDX during the 2016-2020 period. The research method used is a quantitative method using secondary data. The analysis technique used is multiple linear regression analysis using the help of SPSS version 25. The results showed that financial stability as measured by ACHANGE, external pressures measured by leverage ratios, financial targets measured by ROA, as well as the nature of the industry as measured by the ratio of receivables to sales, have a positive coefficient and affect significantly the possibility of fraudulent financial statement, while the effectiveness of monitoring as measured by BDOUT, turnover of external auditors, and changes of directors has The coefficient is positive and does not significantly affect the likelihood of fraudulent financial statement.